Implementasi Nilai-nilai Adab dalam Pembentukan Karakter Santri di PPTQ Nurul Iman - Suyatman, Suyatman; Supono, Eko; Anshory, M. Isa (TSAQOFAH, 2025)
This study is motivated by the importance of internalizing adab values in shaping the character of female students (santriwati) within the pesantren environment, an area that has received limited academic attention. The aim of this research is to describe the implementation of adab values in the daily lives of santriwati at Pondok Pesantren Tahfidzul Qur’an (PPTQ) Nurul Iman. A descriptive qualitative approach was employed, utilizing observation, interviews, and documentation to collect data on the inculcation of values such as politeness, discipline, and responsibility. These values are instilled through habituation strategies, consistent supervision, and exemplary conduct demonstrated by educators and caretakers. The findings reveal that adab values are integrated into the daily routines of santriwati and have become an inherent part of the pesantren culture, significantly shaping their character both in social interactions and in adherence to institutional rules. This study contributes to a deeper understanding of character education based on adab values within the pesantren context and offers practical guidance for similar institutions in strengthening moral and ethical development.